Theories of Learning (Trinity Journal of Management, IT & Media (TJMITM), 2011)
In today's world where there is so much f? learn an~ t,me  is less, the question arises of how effective and efficient  teaching can be made. Teaching is nowadays not only. limite
Keywords: Theories of Learning; Nervousness; Unconditioned